Model of possible cooperation in financial markets in presence of tax on speculative transactions - Francesco Musolino; David Carfi' (Atti della Accademia Peloritana dei Pericolanti : Classe di Scienze Fisiche, Matematiche e Naturali, 2013)
In this paper, we propose an economic and mathematical model to protect the financial markets from speculative attacks, by introducing a tax on financial speculative transactions. By using Game Theory, we focus on the interaction between two general players: a real economic subject (we call Enterprise) acting with hedging scopes and a bank (we call Financial Institute) acting with speculative purposes. We find different equilibria of our game, by considering friendly, selfless, selfish, fearful or aggressive behavior of players; we note that no equilibrium is good for both players, and each of them prevent at least one of the two economic subjects to obtain profits. So, we propose two different transferable utility solutions, in order to achieve a result satisfying both economic subjects and, at the same time, to achieve a condition promoting the stability of the financial markets in which our two players are interacting.